El arte como herramienta pedagógica en la construcción de una cultura de reconciliación y paz (Quaestiones Disputatae: temas en debate, 2021)
Within the educational process it is necessary to approach and generate significantpedagogical experiences that include art, in its different facets such as:  music, dance, theatre and painting, which in some educational institutions of basic, middle and higher education, can be an unexplored field, without recognition that generates social cohesion and construction of communities in peace; The aim is to make methodologically visible the joint work of the educational institution, “San Jerónimo Emiliani de Tunja-Boyacá”, with its members (students, parents, directors, neighbours of the Santa Ana neighbourhood), who become facilitators, mediators, key informants and managers in the research, “Art as a pedagogical tool for the construction of a culture of reconciliation and peace: The case of the San Jerónimo Emiliani school, Tunja”, which allowed the participation of the people, from the staging of community art (painting on poles and murals), in this way art becomes a tool for social dialogue and recognition of problems; therefore for Castro, “art humanises us, art helps us to be sensitive. Otherwise we would not be able to appreciate ourselves”. (Castro, 2017, p. 1); it is necessary to maintain
Keywords: Art, education, meaningful experience, community, participation, peace, dialogue, reconciliation.